Molecular mechanism of human α1A-adrenoceptor inhibition by Mamba snake toxin AdTx1 - Mingyu Shi; Shuhao Zhang; Angqi Zhu; Yosuke Toyoda; Fang Kong; Xiaoou Sun; Xinyu Xu; Chuangye Yan; Xiangyu Liu (Communications Biology)
Abstract There is growing interest in peptide or small protein based drugs targeting G protein-coupled receptors (GPCRs) for improved subtype selectivity over small molecules. Naturally occurring toxins represent rich sources of such ligands. AdTx1 (ρ-Da1a), a three-finger toxin (3FTx) from the green Mamba Snake, selectively binds and antagonizes α-adrenoceptors. Here, we present the cryo-electron microscopy structure of α1A-adrenoceptor in complex with AdTx1. The structure reveals the molecular mechanism of the subtype selectivity and antagonist activity of AdTx1 for α1A-adrenoceptor, which is different from those revealed by the only 3FTx-GPCR structure reported so far, the Muscarinic toxins 7 (MT7) - Muscarinic acetylcholine receptor 1 (M1AChR) structure. Based on the structural information, we further engineered the AdTx1 and enhanced its antagonist activity by introducing three mutations. The results highlight the potential of developing potent toxin drugs towards GPCRs based on the 3FTx scaffold and structural information.